2011
DOI: 10.1158/0008-5472.sabcs11-s1-1
|View full text |Cite
|
Sign up to set email alerts
|

S1-1: A Phase III Randomized Trial of Anastrozole Versus Anastrozole and Fulvestrant as First-Line Therapy for Postmenopausal Women with Metastatic Breast Cancer: SWOG S0226.

Abstract: Background: Anastrozole inhibits the aromatase enzyme-induced estrogen synthesis, and fulvestrant down-regulates estrogen receptors in hormone receptor-positive breast cancer. We hypothesized that the simultaneous disruption of the ligand-receptor axis with concurrent use of these agents may be potentially additive or synergistic in first-line therapy of hormone receptor-positive metastatic breast cancer in postmenopausal women. Materials and Methods: A total of 707 patients were randomized to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the recently presented SWOG-S0226 trial which tested the combination of anastrozole and fulvestrant vs. anastrozole alone for metastatic breast cancer, surprisingly, significant differences were found both in progression-free survival (HR 0.8, 95 % CI: 0.68-0.94; p = 0.007, l " Fig. 6) and, above all, also in overall survival (HR 0.81; 95 % CI: 0.65-1.00; p = 0.049) [62]. This success was achieved almost exclusively in those patients who had not previously received tamoxifen.…”
Section: Biomarkers Pten and Pik3camentioning
confidence: 92%
See 1 more Smart Citation
“…In the recently presented SWOG-S0226 trial which tested the combination of anastrozole and fulvestrant vs. anastrozole alone for metastatic breast cancer, surprisingly, significant differences were found both in progression-free survival (HR 0.8, 95 % CI: 0.68-0.94; p = 0.007, l " Fig. 6) and, above all, also in overall survival (HR 0.81; 95 % CI: 0.65-1.00; p = 0.049) [62]. This success was achieved almost exclusively in those patients who had not previously received tamoxifen.…”
Section: Biomarkers Pten and Pik3camentioning
confidence: 92%
“…Taking the health-care costs into consideration differentiated according to the various types of care offered, there are especially 3 major cost factors: for physiciansʼ services the expenditure in 2008 was 71.5 billion € (27.2 %), for nursing and thera-S0226 trial -Evaluation of the primary endpoint progression-free survival. Adapted after Mehta et al[62].…”
mentioning
confidence: 99%
“…These results are in contrast to the earlier FACT trial, which was similar in design but may have included a larger proportion of "endocrine-insensitive" subjects, as 60% of women enrolled in S0226 had no adjuvant endocrine therapy. Although the results of S0226 are compatible with preclinical observations, the value of the benefit will need to be assessed from a clinical and cost-effectiveness perspective [47].…”
Section: Combining Aromatase Inhibitors and Fulvestrantmentioning
confidence: 96%
“…13 In the second study (S0226), the progression-free survival (hazard rate, 0.80; 95% CI, 0.68–0.94, stratified log-rank P = .007) and overall survival (hazard rate, 0.81; 95% CI, 0.65–1.00; stratified P = .049) were superior with combination anastrozole plus fulvestrant. 14 An unplanned subset analysis of this trial suggested that patients without prior adjuvant tamoxifen experienced the greatest benefit with the combination endocrine therapy. The reason for the divergent outcomes in the 2 studies is not known.…”
Section: Combination Endocrine Therapy An Option For First-line Treatmentioning
confidence: 96%
“…Because of the contradictory results of the FACT 13 and S0226 14 trials, the NCCN Breast Cancer Panel has not made specific recommendations for including combination endocrine therapy in the main algorithm of the guidelines. However, the panel included a footnote on algorithm page BINV-18 (see page 823) stating, “A single study (S0226) in women with hormone receptor–positive breast cancer and no prior chemotherapy, biological therapy, or endocrine therapy for metastatic disease demonstrated that the addition of fulvestrant to anastrozole resulted in prolongation of time to progression (hazard rate for recurrence, 0.80; 95% CI, 0.68–0.94; stratified log-rank P =.007) and improvement in overall survival (hazard rate, 0.81; 95% CI, 0.65–1.00; stratified log-rank P = .049).…”
Section: Combination Endocrine Therapy An Option For First-line Treatmentioning
confidence: 99%